Development and validation of a questionnaire to measure family social capital - Carrillo-Álvarez, Elena (SSM Popul Health, 2019)
The development and psychometric validation of instruments to measure social capital remains a priority in the field. The aim of the current study was to develop a Questionnaire on Family Social Capital (FSCQ) for use in an adolescent population and to test its reliability and validity. We followed an exploratory, sequential mixed-methods approach consisting of four steps: (1)item selection based on a conceptual model; (2)expert judgment of the conceptual model; (3)cognitive validation through focus groups; (4)psychometric validation, through principal components analysis (PCA) and confirmatory factor analysis (CFA) to assess construct validity, using Cronbach alpha and ICC to test reliability, and testing rural-urban differences to evaluate discriminant validity. A total of 429 3r and 4th ESO students participated in the study. The resulting 26-item FSCQ demonstrated a second-order model with two dimensions and seven first-order factors. The model showed good internal consistency and reliability, as indicated by the Chi-squared value(χ = 155.834; p = 0.91) and CFI(0.936). Discriminant validity tests showed significantly higher scores for the structural FSC and the total FSC scores for the rural group. We conclude that the instrument is an adequate tool to study family social capital in adolescents.